Codification work in the field of procedural criminal law in Poland in the years 1919–1928 - Koredczuk, Józef (The Opole Studies in Administration and Law, 2020)
In his contribution, the author presents the work on the codification (initially on the Act) of procedural criminal law in Poland in the years 1919–1928. Those works were initially led by the Criminal Department of the Codification Committee, and then by the Criminal Proceedings Section of the Codification Commission. The first period of the work on the criminal procedure law was characterized by some disputes between the members of the Department, i.e. supporters of the classical school (E. Krzymuski) vs. the sociological school (J. Makarewicz), the discussion aiming at defining the relationship of procedural criminal law and substantive criminal law. The work on the draft law was carried out faster after the appointment (on 16 July 1920) of the Criminal Proceedings Section, which in 1924 published the first version of the draft criminal law bill. E. Krzymuski, A. Mogilnicki, Z. Rymowicz and E.S. Rappaport had played the main role in the development of the project. After a very deep criticism in the columns of Gazeta Administracji i Policji Państwowej [The Gazette of State Administration and Police], Ruch Prawniczy, Ekonomiczny i Socjologiczny [The legal, economic and sociological movement] and Palestra [The bar], the project was rejected. Only the second version of the bill prepared in 1925-1926, re-worked by the committee composed of W. Makowski, A. Mogilnicki and S. Śliwiński (appointed by the Minister of Justice), became the basis for the President of the Republic of Poland to adopt the first Polish Code of Criminal Procedure of 19 March 1928.